Depletion of soil organic carbon stocks are larger under plastic film mulching for maize. (2nd January 2019) - Lee, Jeong Gu; Hwang, Hyun Young; Park, Mun Hyeong; Lee, Chang Hoon; Kim, Pil Joo
Abstract : To determine the effect of plastic film mulching (FM) on changes in soil organic carbon (SOC) stocks, the annual C balances were determined by analysing the net ecosystem C budget (NECB), which means the difference between total C input and output, under FM and with no mulching for 2 years. Plots with black FM and no mulching were installed as the main treatment, and chemical and organic fertilizer plots were placed within each main plot as sub‐treatments. In the organic fertilizer treatment, a mixture of barley ( Hordeum vulgare L.) and hairy vetch ( Vicia villosa Roth) was cultivated as a cover crop during fallow seasons, and its whole biomass (9.1–13.9 Mg ha −1, DW) was recycled as green manure. Plastic film mulching significantly increased the maize yield ( p  < 0.001), mainly because of improved soil moisture and temperature conditions. This stimulated growth under FM, increased the net primary production (NPP) of maize by 3.8–4.7 and 5.0–5.2 Mg C ha −1 over no mulching in the chemical and organic fertilizer treatments, respectively. However, FM increased the loss of mineralized C by an average of 2.6 and 3.7 Mg C ha −1 over the no‐mulching plots for the same treatments. Because the whole aboveground biomass of maize was removed, the annual NECB had a large negative value under all treatments. For the chemical fertilizer treatment, the annual NECB was minus 6.1–7.1 Mg C ha −1 year −1 under no mulching, but under FM it decreased to minus 7.9–8.9 Mg C ha −1 year −1 . Cover cropping and its biomass recycling, however, increased the annual NECB by 43–48% and 25–26% with no mulching and FM, respectively. Therefore, cover cropping and the recycling of its biomass and crop residues are more likely to sustain SOC stocks under the FM system. Highlights: Film mulching significantly increased maize yields and net primary production. Film mulching significantly increased respired C loss in soil. Film mulching significantly decreased soil C stock. Cover cropping and incorporation of its biomass increased soil C stock.